Integration of Malangan Mask Puppet Ethnomathematics in E-Comics to Improve Algebra Literacy Skills of VIII Grade Students on The Concept of Sets - Erni Anggraini; Sri Harini; Marhayati Marhayati (Universitas Wiralodra, 2026)
The purpose of this study is to develop learning media in the form of an e-comic based on the ethnomathematics of the Malangan Masked Wayang to improve algebraic literacy, especially in the material of set theory. The main problem underlying this study is the low ability of students to abstract mathematical concepts from real contexts into algebraic symbols. Ethnomathematics in this study is through the classification of Malangan Masked Wayang characters based on mask colors, character traits, and clothing attributes. Explicitly, these cultural elements are constructed into set theory concepts, including universal sets, subsets, and set operations (intersections and unions). The research method used is R&D with the ADDIE model to describe the validity, effectiveness, and practicality of the development product. The effectiveness test procedure uses a Paired Sample t-test with a significance level of 5%. The results obtained on average on the e-comic validation score are 94% which means the data is very valid. In terms of practicality, the e-comic product based on the ethnomathematics of the Malangan Masked Wayang has an average of 93.3%, including the very practical category. Then the effectiveness value of e-comics was found to have a fairly large score on the N-gain value, namely 0.64. These results can be concluded that e-comics based on ethnomathematics of Malangan mask puppets have good validity, are very practical, and are quite effective in improving the algebraic literacy of MTs grade VIII students.